2019
DOI: 10.1111/exd.13946
|View full text |Cite
|
Sign up to set email alerts
|

Expression and biological functions of the CCL5‐CCR5 axis in oral lichen planus

Abstract: Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disorder with T cell‐mediated immunological pathogenesis. C‐C motif chemokine ligand 5 (CCL5) and its receptor C‐C motif chemokine receptor 5 (CCR5) play important roles in the activation and recruitment of T cells. This study sought to explore the expression and biological functions of the CCL5‐CCR5 axis in OLP. We examined the expression of the CCL5‐CCR5 axis in the peripheral blood and oral tissue of healthy controls and patients with OLP using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…As reported by previous studies, the abnormal interaction of CCL5/CCR5 has been found in multiple types of inflammation, 61 including hepatitis, atherosclerosis, and microglia inflammation. Some viral infections are also mediated by CCL5/CCR5 axis.…”
Section: Ccl5/ccr5 and Diseasessupporting
confidence: 69%
“…As reported by previous studies, the abnormal interaction of CCL5/CCR5 has been found in multiple types of inflammation, 61 including hepatitis, atherosclerosis, and microglia inflammation. Some viral infections are also mediated by CCL5/CCR5 axis.…”
Section: Ccl5/ccr5 and Diseasessupporting
confidence: 69%
“…To explore whether CCN1 promoted the activation of keratinocytes, we tested the keratinocyte using CCK‐8 assay in HaCaT cells with LPS, mimicked the local inflammatory environment of OLP 13,14 . The CCK‐8 assay showed that keratinocyte proliferation significantly ( P < .05) increased by CCN1 stimulation against control (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10]20 Besides, inflammatory cytokines IL-1β, ICAM1, and CCL5 expression in OLP was reported separately. [12][13][14] However, the data of CCN1 and its related cytokines IL-1β, ICAM1, and CCL5 in OLP are not available so far in the literature. Herein, we showed that altered expression of CCN1 in OLP associated with keratinocyte activation and IL-1β, ICAM1, and CCL5 up-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations